Characterization of stability of contractions - Kérchy László (Acta scientiarum mathematicarum, 2013)
We characterize those sequences of bounded analytic functions, which have the property that an absolutely continuous contraction T is stable (that is the powers Tn converge to zero) exactly when the operators hn(T) converge to zero in the strong operator topology. Our result is extended to polynomially bounded operators too.